Pengaruh Pelatihan Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT Njz Logistik Indonesia Di Tangerang Selatan - Untung Darmawan; Endang Suprapti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract. This study aims to determine the effect of training and work motivation on employee performance at PT NJZ Logistik Indonesia both partially and simultaneously. This research uses quantitative methods with an associative approach. The sampling technique uses saturated sampling with 63 respondents. Data analysis techniques include: data instrument test, classical assumption test, simple linear regression, multiple linear regression, correlation coefficient, and coefficient of determination. Hypothesis testing uses t-test and F-test. The analysis results show: Training partially has a positive and significant effect on employee performance with a simple linear regression equation Y = 16.551 + 0.598X₁. The correlation coefficient value of 0.743 indicates a strong relationship and the coefficient of determination of 55.2% means that performance is influenced by training by 55.2%. This is proven by the t-test obtained t count > t table (8.675 > 1.671) and reinforced by a significant value < 0.05 (0.000 < 0.05). Work motivation partially has a positive and significant effect on employee performance, indicated by a simple linear regression equation Y = 11.422 + 0.728X₂. The correlation coefficient value of 0.746 indicates a strong relationship and the coefficient of determination of 55.6% means that performance is influenced by work motivation by 55.6%. This is proven by the t-test obtained t count > t table (8.744 > 1.671) and reinforced by a significance value < 0.05 (0.000 < 0.05). The results of the study of training and work motivation simultaneously on employee performance, shown by the multiple linear regression equation Y = 9.724 + 0.346X₁ + 0.428X₂, the correlation coefficient value of 0.804 indicates a very strong relationship and the coefficient of determination of 64.6% means that performance is influenced by training and work motivation by 64.6%. This is proven by the F-test hypothesis test results obtained F count > F table (54.760 > 3.143) and reinforced by a significance value < 0.05 (0.000 < 0.05). Thus it is proven that H₀ is rejected and H₁ is accepted